2016
DOI: 10.20517/2347-9264.2016.07
|View full text |Cite
|
Sign up to set email alerts
|

Total nasal septal reconstruction using costal cartilage in difficult cases of secondary septoplasty

Abstract: Rhinoplasty and septal reconstruction often require the use of cartilage grafts. Complete nasal septal reconstruction may be required in very specific situations like difficult secondary septoplasty or severely deformed post traumatic noses. Usually in these cases the septal cartilage or bone is insufficient for septal reconstruction. The authors hereby describe a new technique of complete septal reconstruction by using the 7th rib (costal) cartilage combined with author's ingenious technique to prevent warpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“… The comparison of total displacement between standard and new techniques, under loading force of 20 g (a) standard technique of 10 x 10 mm (b) design A: septal support graft (invented technique in this study) (c) design B: straight C-shaped [ 17 ] (d) design C: slope C-shaped [ 17 ]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… The comparison of total displacement between standard and new techniques, under loading force of 20 g (a) standard technique of 10 x 10 mm (b) design A: septal support graft (invented technique in this study) (c) design B: straight C-shaped [ 17 ] (d) design C: slope C-shaped [ 17 ]. …”
Section: Resultsmentioning
confidence: 99%
“…The study explored alternative designs based on a previously developed technique in a clinical study. These designs, referred to as C-shaped septal struts (design B and C, Fig 14(C) and 14(D)) , incorporate two vertical limbs on both ends, which have been previously proposed in clinical studies without computational evidence [ 17 ]. The computational analysis showed that the C-shaped septal struts and septal support graft had better strength than the standard method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation